Convertible metal-backed glenoid in total shoulder arthroplasty: a single-centre case series with minimum 15 years’ follow-up - Riccardo Ranieri; Mario Borroni; Giacomo Delle Rose; Marco Conti; Raffaele Garofalo; Alessandro Castagna (Bone & Joint Open)
Aims: The aim of this study was to report long-term clinical outcomes of a modern convertible metal-backed glenoid (MBG) in total shoulder arthroplasty (TSA). Methods: After a minimum of 15 years, a previously studied cohort of 35 patients who received a modern convertible MBG during the period 1996 to 2005 was contacted for clinical and radiological follow-up. At last follow-up, patients were evaluated radiologically and clinically according to the Constant Score, Simple Shoulder Test, and visual analogue scale for pain. Complications and revisions were recorded, and survival analysis was performed. Results: At the last follow-up, 20 patients were contacted. Of these, 15 patients had experienced at least one complication, and ten underwent revision surgery. The mean time to revision was 13.8 years (7 to 20). Cuff failure was the most common complication. Conversion to reverse shoulder arthroplasty, while maintaining the baseplate, was possible in five cases, with good results. In patients in whom the baseplate was removed, revision was performed significantly later (18.4 vs 11.1 years; p = 0.016). The general revision-free survival was 73% (95% CI 49.5 to 87.3) at 15 years and 38% (95% CI 11.8% to 64.3%) at 20 years, while MBG revision-free survival was 96.0% (95% CI 74.8% to 99.4%) at 15 years and 54% (95% CI 16.2% to 80.8%) at 20 years. Clinical scores showed a negative trend over time, although not statistically significant. Radiologically, polyethylene wear was observed in all cases and was complete in 12 out of 19 cases, and five glenoids were ‘at risk’ for loosening. Conclusion: At long-term follow-up, convertible MBG-TSA revealed a high rate of complications and revision surgery, mainly due to soft-tissue failure and polyethylene wear occurring with time. Prompt conversion to RSA maintaining the baseplate provided good results and a low complication rate. Radiological follow-up at about ten years is strictly recommended and, if metal-to-metal contact is observed, conversion to RSA is advisable. These results emphasize the need for continued research into improving TSA outcomes, especially in cases of MBG usage. Cite this article: Bone Jt Open 2025;6(1):82–92.